Penerapan Metode Tasmi’ dalam Meningkatkan Kualitas Hafalan Al-Qur’an di Pondok Pesantren Putri Tahfidz Al-Ghurobaa’ Tumpangkrasak Jati Kudus - Partono Partono; Shinta Ulya Rizqiyah (MA'ALIM: Jurnal Pendidikan Islam, 2022)
This study aims to determine: 1) The application of the tasmi’ tasmi' method in improving the quality of memorizing the Qur'an in the female Islamic boarding school Tahfidz Al-Ghurobaa' 2) The effectiveness of the application of the tasmi' method in improving the quality of memorizing the Qur'an at the female Islamic boarding school. Tahfidz Al-Ghurobaa' 3) What are the factors that support and hinder the application of the tasmi' method at the Tahfidz Al-Ghurobaa' Islamic Boarding School for Girls. This research includes field research using a qualitative approach. The data collection techniques were obtained from participant observation, interviews, and documentation. While the data analysis of this research includes data collection, data reduction, data presentation and drawing conclusions. The results of the study show that (1) The application of the tasmi' method can improve the quality of memorizing the Qur'an because it can detect errors in reading. (2) The tasmi' method is an effective method to apply because it can improve the quality of memorizing the Qur'an (3) The achievement of the tasmi' method is influenced by inhibiting and supporting factors. Supporting factors include creating a Qur'anic nuanced environment, always repeating readings with friends, and having an ideal age, while the inhibiting factors are laziness, lack of istiqomah, and difficulty in managing time.Keywords: Tasmi' Method, Memorizing Al-Qur'an, Quality of Memorizing Al-Qur'an